2020
DOI: 10.1017/s0029665120004280
|View full text |Cite
|
Sign up to set email alerts
|

The impact of herbs and spices on the appreciation of low-salt legume-based dishes

Abstract: AbstractIntroductionDespite the well-documented health benefits of a dietary pattern higher in plant-based food such as legumes, their consumption remains low. Knowing that taste is the first factor in consumers’ food choice, flavoring of legumes using blends of herbs and spices (H&S) is an interesting approach to increase their consumption. This study examines the effect of H&S on the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Many studies have shown the effectiveness of herbs and spices on increasing saltiness of sodium-reduced foods or masking the bitter aftertaste of alternative salts such as potassium chloride. H&S were a sensory acceptable addition to foods like legume based dishes (Vannereux et al, 2020), beef hamburger (Carvalho et al, 2017), soups (Wang et al, 2014) and bologna sausage (Carraro et al, 2012), but H&S enriched product had similar acceptance in relation to the control product. Kohri et al (2020) assessed the potential effect of basil, rosemary, parsley, anise and oregano on the enhancement of saltiness perception in a saline solution.…”
Section: Taste Enhancers: Herbs and Spicesmentioning
confidence: 98%
“…Many studies have shown the effectiveness of herbs and spices on increasing saltiness of sodium-reduced foods or masking the bitter aftertaste of alternative salts such as potassium chloride. H&S were a sensory acceptable addition to foods like legume based dishes (Vannereux et al, 2020), beef hamburger (Carvalho et al, 2017), soups (Wang et al, 2014) and bologna sausage (Carraro et al, 2012), but H&S enriched product had similar acceptance in relation to the control product. Kohri et al (2020) assessed the potential effect of basil, rosemary, parsley, anise and oregano on the enhancement of saltiness perception in a saline solution.…”
Section: Taste Enhancers: Herbs and Spicesmentioning
confidence: 98%